Peran Keterampilan Sosial dalam Meningkatkan Prestasi Akademik Siswa Berkebutuhan Khusus di Sekolah Dasar Inklusif - Citra Wahyuni; Frieda Maryam Mangunsong (Jurnal Ilmiah Psikologi MIND SET, 2018)
Some previous studies showed that students with special education needs (SEN) in inclusive elementary schools experience many problems, including academic problems. One individual factor that can affect the academic achievement of students with SEN is social skills. This study aimed to understand the correlation between social skills and academic achievement of students with SEN in inclusive elementary schools. We also examined demographic variables of children (children’s gender, type of disability, and level of impairment) that can affect children’s social skills. Participants in this study were 210 classroom teachers who teach 365 students with SEN inclusive elementary schools in Jakarta. Participants were obtained by convenience sampling technique, with sample from 17 public and five private inclusive elementary schools in Jakarta. This study was conducted using a quantitative method and correlational non-experimental design, and used pearson correlation, independent t-test, and one-way ANOVA as statistical test. Our results showed that social skills have a significant correlation to academic achievement of children with SEN. The only demographc variables that affected parental involvement was the level of impairment experienced by children. The results suggest that social skills are an important aspect to be developed in students with SEN.